Development Of Cognitive Mechanisms (In the Example of Future Geography Teachers) - Rajabov Furkat Turakulovich (Genius Journals, 2022)
This article analyzes the development of cognitive mechanisms on the example of future geography teachers. In addition, this article discusses the role of pedagogical practice in training future teachers.
Keywords: Future geography teachers; professional training; geographic space; curriculum